Methadone Inhibits Viral Restriction Factors and Facilitates HIV Infection in Macrophages - Wang, Mei-Rong; Wu, Di-Di; Luo, Fan; Zhong, Chao-Jie; Wang, Xin; Zhu, Ni; Wu, Ying-Jun; Hu, Hai-Tao; Feng, Yong; Wang, Xu; Xiong, Hai-Rong; Hou, Wei (Frontiers in Immunology, 2020)
Opioid abuse alters the functions of immune cells in both in vitro and in vivo systems, including macrophages. Here, we investigated the effects of methadone, a widely used opioid receptor agonist for treatment of opiate addiction, on the expression of intracellular viral restriction factors and HIV replication in primary human macrophages. We showed that methadone enhanced the HIV infectivity in primary human macrophages. Mechanistically, methadone treatment of macrophages reduced the expression of interferons (IFN-β and IFN-λ2) and the IFN-stimulated anti-HIV genes (APOBEC3F/G and MxB). In addition, methadone-treated macrophages showed lower levels of several anti-HIV microRNAs (miRNA-28, miR-125b, miR-150 and miR-155) compared to untreated cells. Exogenous IFN-β treatment restored the methadone-induced reduction in the expression of the above genes. These effects of methadone on HIV and the antiviral factors were antagonized by pretreatment of cells with naltrexone. These findings provide additional evidence to support further studies on the role of opiates, including methadone, in the immunopathogenesis of HIV disease.